Whether to decentralize and how to decentralize? The optimal fiscal federalism in an endogenous growth model - Xiaodong Chen; Haoming Mi; Peng Zhou (Cardiff University, Cardiff Business School, 2023)
We develop an endogenous growth model with public consumption and infrastructure services provided by two-tier governments. Growth performance and welfare implication are compared under the centralized and decentralized fiscal federal systems. In general, there is a trade-off between welfare and growth due to conflicts of interest and asymmetric information between central and local governments. By numerical simulations, we show that the optimal fiscal federalism should impose restrictions on expenditure-GDP ratio, rather than on expenditure-budget ratio or central-local expenditure ratio, because expenditure-GDP ratio can align the incentives of the two-tier governments. Furthermore, it is suggested that decentralized fiscal systems are generally superior to the centralized system because the efficiency loss overweighs the agency cost. The model is then applied to analyzing different growth experiences in the West and China by institutional and cultural differences.
Keywords: E61; E62; H1; H5; O41; R5; 330; Fiscal Federalism; Decentralization; Economic Growth; Social Welfare